BERNARD CORNWELL: A LITERATURA FOR “TOUGH GUYS”? - Soares, Isabelle; Silva, Edson Santos (Inventário, 2024)
The reading of the literary series Saxon Stories (2004-), by the British author Bernard Cornwell, incites reflections about the relations between Scandinavians and Anglo-Saxons in the British territory in the ninth century, as it presents a panorama of this historical moment. Fiction and history clash to represent significant moments of the time reported. From this, the main objective of this article is to trace debates about the memories that flow in the work concerning its production context, in the contempore, that surround the author and that imply Gender Study issues exteriorized and interiorized by the work under study. Starting from the idea proposed by the blogger Hyperactive Sedentary (2010), that the work of the British author, Bernard Cornwell, is literature made for "males", we seek to analyse moments of the narrative present in the first three volumes of Saxon Stories, in order to understand the motivation for such assertion and, if possible, refute it. Our analysis is grounded in Badinter (1992), Connel and Messerschmidt (2013), Dumézil (2013), Mingo (2017) and Langer (2007; 2017).